Dynamics of hepatitis B virus quasispecies in association with nucleos(t)ide analogue treatment determined by ultra-deep sequencing. - Norihiro Nishijima; Hiroyuki Marusawa; Yoshihide Ueda; Ken Takahashi; Akihiro Nasu; Yukio Osaki; Tadayuki Kou; Shujiro Yazumi; Takeshi Fujiwara; Soken Tsuchiya; Kazuharu Shimizu; Shinji Uemoto; et al. (PLoS ONE, 2012)
Background and aims Although the advent of ultra-deep sequencing technology allows for the analysis of heretofore-undetectable minor viral mutants, a limited amount of information is currently available regarding the clinical implications of hepatitis B virus (HBV) genomic heterogeneity. Methods To characterize the HBV genetic heterogeneity in association with anti-viral therapy, we performed ultra-deep sequencing of full-genome HBV in the liver and serum of 19 patients with chronic viral infection, including 14 therapy-naïve and 5 nucleos(t)ide analogue(NA)-treated cases. Results Most genomic changes observed in viral variants were single base substitutions and were widely distributed throughout the HBV genome. Four of eight (50%) chronic therapy-naïve HBeAg-negative patients showed a relatively low prevalence of the G1896A pre-core (pre-C) mutant in the liver tissues, suggesting that other mutations were involved in their HBeAg seroconversion. Interestingly, liver tissues in 4 of 5 (80%) of the chronic NA-treated anti-HBe-positive cases had extremely low levels of the G1896A pre-C mutant (0.0%, 0.0%, 0.1%, and 1.1%), suggesting the high sensitivity of the G1896A pre-C mutant to NA. Moreover, various abundances of clones resistant to NA were common in both the liver and serum of treatment-naïve patients, and the proportion of M204VI mutants resistant to lamivudine and entecavir expanded in response to entecavir treatment in the serum of 35.7% (5/14) of patients, suggesting the putative risk of developing drug resistance to NA. Conclusion Our findings illustrate the strong advantage of deep sequencing on viral genome as a tool for dissecting the pathophysiology of HBV infection.